2018
DOI: 10.1111/sms.13309
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of lower limb stiffness between male and female dancers and athletes during drop jump landings

Abstract: Repetition of jumps in dance and sport training poses a potential injury risk; however, non‐contact landing injuries are more common in athletes than dancers. This study aimed to compare the lower limb stiffness characteristics of dancers and athletes during drop landings to investigate possible mechanisms of impact‐related injuries. Kinematics and kinetics were recorded as 39 elite modern and ballet dancers (19 men and 20 women) and 40 college‐level team sport athletes (20 men and 20 women) performed single‐l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
(87 reference statements)
0
18
0
Order By: Relevance
“…Drop jump depth was designated as the smallest negative vertical center of mass displacement after first landing. Leg stiffness was determined by a spring-mass model (Ward et al, 2019) and was calculated using the following formula: Stiffness = GRFmax Depth Force, impulse, power, and stiffness were normalized to body mass.…”
Section: 𝑃 = 𝑊 − 𝑊 δ𝑡mentioning
confidence: 99%
“…Drop jump depth was designated as the smallest negative vertical center of mass displacement after first landing. Leg stiffness was determined by a spring-mass model (Ward et al, 2019) and was calculated using the following formula: Stiffness = GRFmax Depth Force, impulse, power, and stiffness were normalized to body mass.…”
Section: 𝑃 = 𝑊 − 𝑊 δ𝑡mentioning
confidence: 99%
“…Males had greater vertical leg stiffness compared to females, which occurred with a lower center of mass (COM) vertical displacement per height and greater peak GRF per body weight [26]. A previous study showed that males had greater ankle joint stiffness, a lower initial plantar flexion angle, lower ankle ROM, and greater changes and peaks in ankle moment compared to females [26]. Ankle joint stiffness was thought to be due to a reduced ankle joint ROM during landing.…”
Section: Discussionmentioning
confidence: 99%
“…In this series, 4 dancers had ACL injuries, all of which had occurred during the landing sequence after leaping. For a secure landing, the knee ought to be in a flexion and varus position; landing while the knee is in an extension and valgus position is a risk factor for an ACL injury [9,16,[24][25][26]. Four of the dancers had ACL tears; all of them were Caucasian dancers.…”
Section: Meniscal Tearsmentioning
confidence: 99%